Promotion of investments under Yaounde II - Heinz Langerbein (Intereconomics, 1972)
There are many companies operating within the Common Market to whom the highly favourable conditions for making investments in many African countries, which exist under the Yaounde Agreement, are not known. In the following article the possibilities offered to private investors by Yaounde II for facilitating their ventures are discussed.
Keywords: 330; Africa